Applications of Computational Fluid Dynamics Simulation and Modeling - Bhattacharyya, Suvanjan (IntechOpen, 2022)
This book provides well-balanced coverage of computational fluid dynamics analysis for thermal and flow characteristics of various thermal and flow systems. It presents the latest research work to provide insight into modern thermal engineering applications. It also discusses enhanced heat transfer and flow characteristics.